THE EFFECTS OF THYROXINE HORMONE ON GONADAL MATURATION AND GROWTH OF MALE SPINY LOBSTER (PANULIRUS HOMARUS) - Adiputra, Yudha Trinoegraha; Zairin Jr., Muhammad; Agus Suprayudi, Muhammad; Manalu, Wasmen; ., Widanarni; Brite, Margie (Malaysian Journal of Science, 2020)
The present experiment was designed to find the optimum dose of thyroxine hormone administration to enhance gonadal maturation and growth of male spiny lobster (Panulirus homarus). Maturation study used 30 male spiny lobsters divided into two treatments of thyroxine hormone injection i.e., 0 and 0.1 µg/g BW. Samples were taken to determine parameters of gonadosomatic index (GSI), anatomy and histology of gonads. Growth study used 44 males spiny lobsters divided into 4 treatments of thyroxine injection i.e., 0, 0.1, 0.2, and 0.5 µg/g BW during 70 days of culture. Specific growth rate (SGR), the growth of carapace length (GCL), molted, feed conversion ratio (FCR), and survival rate were observed. Meat qualities of wild and cultured spiny lobsters were measured by proximate and amino acids composition. Results showed that male spiny lobster injected with thyroxine at a dose 0.1 µg/g BW increased GSI (P<0.05), showed a better gonad development and higher number of spermatogonia. Injection of thyroxine hormone at a dose of 0.1 µg/g BW supported the optimum SGR and GCL (P<0.05), FCR, molted and survival rate. The meat quality of wild were better than cultured spiny lobsters as was indicated by the better proximate and amino acids composition (P<0.05).